Interpretation of QS. al-Wāqi’ah [56]: 20-21 as a Solution-Oriented Diet for Nutritional Health: Analysis of Tafsir and Nutritional Science Approaches - Muhammad Raihan Tsani Alkhalish (Fakultas Ushuluddin dan Pemikiran Islam Universitas Islam Negeri Raden Fatah Palembang, 2025)
This article aims to analyze the concept of a health-promoting dietary pattern based on the interpretation of QS. Al-Wāqi‘ah [56]: 20–21 by classical and modern Qur’anic exegetes, alongside perspectives from nutritional health sciences that affirm these interpretations through empirical research. The study employs a thematic approach combined with nutritional science and uses a library research method. The analysis focuses on QS. Al-Wāqi‘ah [56]: 20–21 by examining tafsir sources that offer linguistic explanations of the verses and their relevance to contemporary nutritional discourse, including Tafsīr Mafātīḥ al-Ghayb, Tafsīr al-Munīr, Tafsīr Ma‘ālim al-Tanzīl, and Tafsīr al-Miṣbāḥ. The findings indicate that the interpretations of these verses show meaningful relevance to nutritional health, supported by current scientific studies. In the field of Qur’anic exegesis, the precedence of “fruit” before “meat” in the verse is understood as an indication that fruit is lighter, digests faster, is more easily processed by the body, and can stimulate appetite before the main meal. This interpretation aligns with nutritional science, particularly research from Japan demonstrating that structuring meal order—beginning with vegetables and proteins before carbohydrates—can slow the post-meal rise in blood glucose levels. Thus, the interpretation of this verse can be viewed as offering a practical and beneficial dietary model for maintaining nutritional health.